The impact of exceptional circumstances on personal freedoms: دراسة مقارنة - طالب, مصدق عادل; جاسم, الفارعة عبدالله (Journal of Legal Sciences, 2019)
The safety of state may be threatened by the exceptional circumstances such as the wars and normal disasters. Those circumstances make the state unable to protect the general system by using public rules. So the authority of control organization should expand to control such circumstances. Those authorities should report hasty and definitive steps to encounter such issues. The exceptional circumstances may directly affect the personal rights and freedom that were warranted by the constitution. So the legislator should determine the constraints that were adopted upon them and showed the guarantees of those liberties in order to avoid the unfair decisions and orders.